EPS System of Tractor Automatic Driving: An Improved LMI with Mixed Sensitivity Control Method - Huanxiao Pang; Guangfei Xu; Zhicai Song; Dianbao Zhao; Wenjun Wang; Peisong Diao (Journal of Electrical and Computer Engineering)
Electric power steering (EPS) is widely used in tractor automatic driving because of its good operation stability. However, there is a lack of research about solving robust problems and response ability simultaneously when the tractor encounters emergency steering in harsh fields. The traditional robust controller has poor tracking performance and antidisturbance ability when encountering emergency steering. This paper proposes to add the corresponding mixed sensitivity operator to the corresponding performance index in the controller. By adjusting the amplitude of the mixed sensitivity operator, the tracking performance and the speed of disturbance attenuation can be both adjusted for the tractor EPS system. Simulation and hardware in the loop experiments verify the antidisturbance ability of the controller and the torque tracking performance. The results show that the control method has strong robustness and robust stability, which can meet the practical requirements. Also, the power steering characteristic of the H∞ controller with hybrid sensitivity design method is better than that of an unoptimized one, and its robustness is better, and under external pavement interference, the following ability is stronger for the ideal hand torque and the steering is more stable.